IRFAN HABIB & VIVEKANAND JHA. MAURYAN INDIA. 9TH EDITION. A PEOPLE’S HISTORY OF INDIA VOL. 5 - Matthew Gray Marsh (Journal of Ancient History and Archaeology)
Irfan Habib & Vivekanand Jha, Mauryan India. 9th Edition. A People’s History of India Vol. 5. New Delhi: Tulika Books, 2019, x + 189p., ISBN 978-93- 82381-62-4.